Enzymatic Versus Chemical Conversion of Soybean Hull to Useful Products - Kaur, Taranvir (My University, 2017)
Existing study was focused on the utilization of soybean by-product waste that is soy hull conversion into useful products for human use. Commercially, the soybean hulls were used for animal feedstock and production of various useful industrial products. An initiative has been done to utilize soybean hull as source of growth for gut probiotic bacteria that are useful for humans, so that the all the major by-product produced by the soybean processing industries can be utilized and the waste results into another useful consumable product. The chemical and enzyme assisted (pectinase and cellulase) methods have been implemented to observe the superficial changes in the soy hull through SEM. All the three samples (two treated with enzymes such as cellulase and pectinase and one with NaOH) were analyzed for growth of micro-organisms like Lactobacillus casei, Saccharomyces cerevisiae and Aspergillus niger showing that soy hull can be used as a substrate for its utilization and substitution as a growth medium for the growth of useful microorganisms.
Keywords: Soybean, soybean hull, enzymatic degradation, pectinase, cellulase, chemical conversion; micro-organisms growth, Lactobacillus casei, Sachhromyces cerevisae, Aspergillus niger